(untitled) (International Journal of Environmental Sciences, 2025)
The Bhagavad Gita is that work of the Hindu literature often known to portray an enduring lesson on selflessness, duty, and leadership. Since the establishment of such profound principles, it has been resonant to leaders of all cultures and eras. This paper analyzes the effect that the Bhagavad Gita-the Hindu text-can have on the development in Frederick Winslow Taylor’s ideas on the science of management. Even though the scientific management had its importance on efficiency and productivity, Gita highlighted the point of ethics and welfare of the employees. The paper analyzes the teachings of the Gita and will argue that the ideas this text present could have helped with assistance to Taylor’s Scientific Management principles. It will explore how the ideas of the Gita may help in the implementation of the principles set by the Scientific Management-its ability to create a more compassionate workplace environment, promote moral decisions, enhance happiness among staff, and keep the eye on the future. This study concludes that Bhagavad Gita can be a source to aid modern leaders towards balancing efficiency, ethics, and human-centered approaches to doing things. This paper sustains an argument through contrasting Krishna’s spiritually oriented leadership advice to Arjuna with Taylor’s mechanical approach in managing people with a focus on efficiency to merge empowerment with scientific management with the aim of deriving a more holistic and human-cantered paradigm in leadership.